The Holy Bible in its Arabic Language among the Orthodox Copts – Contributions and Issues - Benbekhma , Nassim; Chafia , Ceddik (Journal of Ecohumanism, 2025)
The Holy Bible has been transmitted to the languages of the world through translation, which is the safest bridge to reach all people regardless of their different languages and tongues. Since Arabic is one of these languages, it is only natural that the biblical text be translated into it as well, so that it may reach Arabic speakers. Numerous Arabic translations have emerged since the era of printing, and they have been distributed among different churches: Protestant, Catholic, and Orthodox. In this context, the present study aims to trace the transmission of the biblical text to the Coptic Orthodox Church in its Arabic language. The research adopts both a descriptive-analytical method and a critical-comparative approach. A number of conclusions were reached, the most important of which are: There is a significant theological and historical relationship between translation and the Holy Bible. The Protestant churches have carried out the most extensive translation and printing work of the biblical text. The Coptic Orthodox Church does not possess an official, complete Arabic translation of the Holy Bible.